2001
DOI: 10.2337/diabetes.50.2007.s125
|View full text |Cite
|
Sign up to set email alerts
|

Sialylated form of the neural cell adhesion molecule (NCAM): a new tool for the identification and sorting of beta-cell subpopulations with different functional activity.

Abstract: To clarify the relationship between variations in ␤-cell mass and pancreatic function, we investigated the possibility to analyze, quantify, and sort ␤-cell subpopulations with different functional maturity. To this aim, we tested the reliability of the sialylated form of neural cell adhesion molecule (NCAM) (PSA-NCAM) as a marker of ␤-cell functional activity. Islet cells isolated from adult rats were analyzed for their PSA-NCAM abundance using an anti-PSA-NCAM antibody. We found that PSA-NCAM is expressed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 24 publications
1
29
1
1
Order By: Relevance
“…No PSA-NCAM signal was detected in CK19-positive duct cells (Fig 1d). These results are different from a previous report [7], where PSA-NCAM expression was restricted to beta cells only in rats. This is another example of interspecies variation between rodent and human islets.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…No PSA-NCAM signal was detected in CK19-positive duct cells (Fig 1d). These results are different from a previous report [7], where PSA-NCAM expression was restricted to beta cells only in rats. This is another example of interspecies variation between rodent and human islets.…”
Section: Resultscontrasting
confidence: 99%
“…It thus appears that although PSA-NCAM immunoreactivity is detected in all islet cell types, the affinity of the antibody is much higher against beta cells. In the rat, high PSA-NCAM specifically characterises a subpopulation of functionally active beta cells [7]. It is thus possible that the observed enrichment is due to the selection of a population of beta cells with high PSA-NCAM expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice were killed, and islets of Langerhans were isolated after collagenase digestion of the pancreas as previously described (47). Briefly, the pancreatic duct was ligated distally and injected with an ice-chilled solution of 630 units/ml collagenase (Type V collagenase; SigmaAldrich) and 5.5 mM glucose in Hank's balanced salt solution (HBSS).…”
Section: Methodsmentioning
confidence: 99%
“…In some studies mainly the NCAM-140 isoform is reported [7,25,28,29] whereas others report that mainly NCAM-120 is expressed in adult islets and expression of NCAM-140 is found only during development and in tumours [26,27]. In beta cells, NCAM has been suggested to be involved in the organisation of biosociology in the islets of Langerhans [26], in beta cell functional activity measured as insulin release [30], and also in natural killer T cell-induced beta cell death [31]. Furthermore, in mouse pancreatic tumour beta cells, NCAM has been shown to activate a Src-kinase and to bind and activate FGFR [32].…”
Section: Introductionmentioning
confidence: 99%